2000
DOI: 10.1084/jem.191.8.1319
|View full text |Cite
|
Sign up to set email alerts
|

A Novel B Lymphocyte–Associated Adaptor Protein, Bam32, Regulates Antigen Receptor Signaling Downstream of Phosphatidylinositol 3-Kinase

Abstract: We have identified and characterized a novel src homology 2 (SH2) and pleckstrin homology (PH) domain–containing adaptor protein, designated Bam32 (for B cell adaptor molecule of 32 kD). cDNAs encoding the human and mouse Bam32 coding sequences were isolated and the human bam32 gene was mapped to chromosome 4q25–q27. Bam32 is expressed by B lymphocytes, but not T lymphocytes or nonhematopoietic cells. Human germinal center B cells show increased Bam32 expression, and resting B cells rapidly upregulate expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 78 publications
(114 reference statements)
10
136
1
Order By: Relevance
“…Additional work is required to distinguish whether phosphorylation alters the intramolecular conformation of PLC␥1 (24), its substrate recognition (12) or protein/ protein interactions that are required for activation (25). Furthermore, although we have shown that Y775 is phosphorylated after TCR engagement in human peripheral T cells and mouse CD4 ϩ T cells, the role that Y775 plays in PLC␥1 activation during T and B cell development and lymphocyte activation in vivo remains to be confirmed.…”
Section: Both Y775 and Y783 Are Required For Plc␥1-dependent Gene Tramentioning
confidence: 99%
“…Additional work is required to distinguish whether phosphorylation alters the intramolecular conformation of PLC␥1 (24), its substrate recognition (12) or protein/ protein interactions that are required for activation (25). Furthermore, although we have shown that Y775 is phosphorylated after TCR engagement in human peripheral T cells and mouse CD4 ϩ T cells, the role that Y775 plays in PLC␥1 activation during T and B cell development and lymphocyte activation in vivo remains to be confirmed.…”
Section: Both Y775 and Y783 Are Required For Plc␥1-dependent Gene Tramentioning
confidence: 99%
“…To visualize Bam32 in intact cells, we used a mammalian plasmid construct encoding Bam32 fused to the fluorescent marker protein, EGFP (14). This construct was transiently expressed in human BJAB cells, and the cells were stimulated with rhodamine-labeled F(abЈ) 2 anti-IgM sera to trigger BCR signaling and internalization (Fig.…”
Section: Bam32 Is Recruited To the Plasma Membrane And Redistributes mentioning
confidence: 99%
“…BJAB cells were transfected with Bam32-enhanced GFP (EGFP) as described previously (14) and then stimulated for indicated time periods with 10 g/ml unlabeled or rhodamine-labeled goat anti-human IgM sera (10 g/ml) at 37°C. Cells were washed twice and fixed with 3.7% paraformaldehyde, permeabilized with PBS containing 1% BSA and 0.05% saponin (wash buffer), intracellularly stained with primary Abs for 30 min, and then washed in wash buffer.…”
Section: Fluorescence Microscopic Analysismentioning
confidence: 99%
See 2 more Smart Citations